Pemberian Muscle Energy Technique dan Strain Counterstrain Dapat Meningkatkan Luas Gerak Sendi pada Kasus Nyeri Punggung Bawah - Nurul Halimah; Angria Pradita; Mokhtar Jamil (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Low Back Pain can be caused by a series of daily routines regardless of body position. The method of physiotherapy intervention in non-specific cases of low back pain is the provision of muscle energy technique and strain counterstrain. The purpose of this study was to determine the comparison of giving muscle energy technique and strain counterstrain to increase joint range of motion in cases of low back pain. The research design used was a randomized pretest–posttest control group. The research subjects were 40 respondents who were selected by purposive sampling technique. The movements assessed were lateral flexion and extension. The range of motion of the lumbar joints measured using an inclinometer, includes the extent of motion of the lumbar extension and lateral flexion. If the joint range of motion of the lumbar extension and lateral lumbar flexion is <25°, it is said to be limited. Statistical tests were performed using the Mann-Whitney U test. In the lateral flexion group with muscle energy technique intervention, p = 0.00, while in the extension group with muscle energy technique intervention, p = 0.00. In the lateral flexion group with the intervention of a counterstrain strain, p = 0.00 was obtained, while in the extension group with the intervention of a counterstrain strain, it was obtained p = 0.00. The results of the difference test between the muscle energy technique intervention and the counterstrain strain on lateral flexion movements showed p = 0.506-0.863, while the results of the differences in muscle energy technique and counterstrain strain in lateral movements showed p = 0.014-0.534, which means there is no difference between muscle therapy energy tecnique and strain counterstrain in lateral flexion and extension movements. Intervention of muscle energy technique and strain counterstrain can significantly increase joint range of motion.Keywords: low back pain; muscle energy technique; counterstrain ABSTRAK Low back pain dapat disebabkan oleh rangkaian rutinitas sehari-hari tanpa memperhatikan posisi tubuh. Metode intervensi fisioterapi pada kasus non spesifik low back pain adalah pemberian muscle energy tecnique dan strain counterstrain. Tujuan dari penelitian ini adalah untuk mengetahui perbandingan pemberian muscle energy technique dan strain counterstrain pada peningkatan luas gerak sendi pada kasus nyeri punggung bawah. Rancangan penelitian yang digunakan adalah randomized pretest–posttest control group. Subyek penelitian adalah 40 responden yang dipilih dengan teknik purposive sampling. Gerakan yang dinilai adalah lateral fleksi dan ekstensi. Luas gerak sendi lumbal yang diukur menggunakan inclinometer, mencakup luas gerak ekstensi dan lateral fleksi lumbal. Jika luas gerak sendi ekstensi lumbal dan lateral fleksi lumbal <25°, maka dikatakan terbatas. Uji statistik dilakukan menggunakan uji Mann-Whitney U. Pada kelompok lateral fleksi dengan intervensi muscle energy tecnique didapatkan p = 0,00, sedangkan pada kelompok ekstensi dengan intervensi muscle energy tecnique didapatkan p = 0,00. Pada kelompok lateral fleksi dengan intervensi strain counterstrain didapatkan p = 0,00, sedangkan pada kelompok ekstensi dengan intervensi strain counterstrain didapatkan p = 0,00. Hasil uji perbedaan antara intervensi muscle energy tecnique dan strain counterstrain pada gerakan lateral fleksi menunjukkan p = 0,506-0,863, sedangkan hasil uji perbedaan muscle energy tecnique dan strain counterstrain pada gerakan lateral menunjukkan p = 0,014-0,534, yang artinya tidak terdapat perbedaan antara terapi muscle energy tecnique dan strain counterstrain pada gerakan lateral fleksi maupun ekstensi. Intervensi muscle energy tecnique maupun strain counterstrain secara signifikan dapat meningkatkan luas gerak sendi.Kata kunci: low back pain; muscle energy tecnique; strain counterstrain